Effect of Reynolds Number on Minor Loss Coefficient for 3 Different Brands of Ball Valves - Tan, Khai Boon; Idris, Ahmad Fu'ad (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project objective was to determine the effect of Reynolds number on the valve loss coefficient for three different brands of ball valves. An apparatus was designed and fabricated to investigate the relationship between the minor loss coefficient and Reynolds number. The apparatus with a ball valve was used to conduct an experiment, collecting around forty raw data for each brand of ball valve. From raw data, the equations related to fluid flow were used to determine the value of the Reynolds number and minor loss coefficient of a ball valve. The analysed results from the experiment showed that the value of the minor loss coefficient is inversely proportional to the Reynolds number for three different brands of ball valves. Different geometries of ball valves result in different minor loss coefficients. Correlation and regression methods were applied to determine the best relationship between the minor loss coefficient and the Reynolds number. The result showed all three ball valves have a strong negative correlation between two variables and a cubic regression model was identified as the best model to describe the relationship for each of the ball valves.